Enhancing Islamic Job Satisfaction in the Midst of Pandemic Era: The Role of Leadership - Firmansah, Yayan; Rusli, Lathiefa; Pamujo, Bagas Bambang (INOVATOR, 2024)
Job satisfaction has been the foundation for the effectiveness of an organization since it can affect the quality of work of employees. Satisfied employees are the evidence that the organization has appreciated their works. Given this fact, however, little research has been done on employee Islamic job satisfaction. Thereby, this study aims to examine and analyze the Islamic job satisfaction of employees and the factors that influence it, which is leadership. The method used in this research is quantitative. Data were collected from 80 respondents. The results of the analysis show that transformational leadership has an effect on Islamic job satisfaction, while transactional leadership is in on the contrary.